Monitoring of Marine Biofilm Formation Dynamics at Submerged Solid Surfaces With Multitechnique Sensors - Grzegorczyk, Maciej; Pogorzelski, Stanisław Józef; Pospiech, Aneta; Boniewicz-Szmyt, Katarzyna (Frontiers in Marine Science, 2018)
Biofouling on artificial and biotic solid substrata was studied in several locations in near-shore waters of the Baltic Sea (Gulf of Gdansk) during a three-year period with contact angle wettability, confocal microscopy and photoacoustic spectroscopy techniques. As a reference, the trophic state of water body was determined from chemical analyses according to the following parameters: pH, dissolved O2, phosphate, nitrite, nitrate, ammonium concentrations, and further correlated to the determined biofilm characterizing parameters by means of Spearman's rank correlation procedure. Biofilm adhesive surface properties (surface free energy, work of adhesion) were obtained with the contact angle hysteresis (CAH) approach using an automatic captive bubble solid surface wettability sensor assigned for in-situ, on-line, and quasi-continuous measurements of permanently submerged samples (Pogorzelski et al., 2013; Pogorzelski and Szczepanska, 2014). From confocal reflection microscopy (COCRM) data, characteristic biofilm structural signatures such as biovolume, substratum coverage fraction, area to volume ratio, spatial heterogeneity, mean thickness, and roughness) were determined at different stages of microbial colony development. Photosynthetic properties [photosynthetic energy storage (ES), photoacoustic amplitude and phase spectra] of biofilm communities exhibited a seasonal variation, as indicated by a novel closed-cell type photoacoustic spectroscopy (PAS) system. Mathematical modeling of a marine biofilm under steady state was undertaken with two adjustable parameters, of biological concern i.e., the specific growth rate and induction time, derived from simultaneous multitechnique signals. A set of the established biofilm structural and physical parameters could be modern water body trophic state indexes.